2021
DOI: 10.1590/0034-761220200843
|View full text |Cite
|
Sign up to set email alerts
|

Impacto das variáveis socioeconômicas no desempenho do Enem: uma análise espacial e sociológica

Abstract: Resumo O objetivo deste trabalho é identificar variáveis com maior impacto no desempenho dos municípios no Exame Nacional do Ensino Médio (Enem), tanto para a prova objetiva quanto para a redação, com base em técnicas de estatística espacial, que permite analisar a dinâmica da influência territorial, e da perspectiva da sociologia da educação. Pretende-se mensurar o grau de importância de cada categoria de variáveis para a média e a variância das notas do Enem. Para isso, utilizam-se modelos estatísticos e geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(16 reference statements)
0
2
0
1
Order By: Relevance
“…For Azevedo (2021), socio-economic inequalities have a very clear expression in the education system, translating into high levels of failure and early school leaving. Corroborating this idea, the results of the study by Melo et al (2021) show that the socioeconomic status of families has a strong relationship with student performance, reflecting such an association. Similarly, the research of Couto et al (2020) revealed that students' families' socio-economic status and socio-economic level of the school have significant predictive power regarding students' performance in science, mathematics and reading, whose explained variation ranges between 20% and 24%, depending on the domain.…”
Section: Scientific Literacy Level According To Socio-economic Level ...mentioning
confidence: 79%
See 1 more Smart Citation
“…For Azevedo (2021), socio-economic inequalities have a very clear expression in the education system, translating into high levels of failure and early school leaving. Corroborating this idea, the results of the study by Melo et al (2021) show that the socioeconomic status of families has a strong relationship with student performance, reflecting such an association. Similarly, the research of Couto et al (2020) revealed that students' families' socio-economic status and socio-economic level of the school have significant predictive power regarding students' performance in science, mathematics and reading, whose explained variation ranges between 20% and 24%, depending on the domain.…”
Section: Scientific Literacy Level According To Socio-economic Level ...mentioning
confidence: 79%
“…Furthermore, several studies have demonstrated the association between socio-economic inequalities and high levels of school failure (Azevedo 2021;Couto et al 2020;Jaloto and Primi 2021;Melo et al 2021;Pinto 2021;Sudbrack and Fonseca 2021). Jaloto and Primi (2021), for example, state that in all of the studies reviewed in their research, socio-economic status was positively associated with student performance.…”
Section: Scientific Literacy Level According To Socio-economic Level ...mentioning
confidence: 99%
“…O resultado mostrou que o efeito negativo das condições climáticas, particularmente da temperatura, não é substancial nem conclusivo para justificar o desempenho na prova. Melo et al (2022), por outro lado, buscaram identificar variáveis com maior impacto no desempenho dos municípios no ENEM com base em técnicas de estatística espacial e na perspectiva da sociologia da educação. Os resultados apresentados sugerem que questões socioculturais e econômicas podem ser fatores importantes quanto às desigualdades de desempenho dos estudantes em avaliações.…”
unclassified